2011
DOI: 10.1371/journal.pone.0025448
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Exposure to Low Dose Bisphenol A Alters Social Behavior in Juvenile Mice

Abstract: Bisphenol A (BPA) is a man-made compound used to make polycarbonate plastics and epoxy resins; public health concerns have been fueled by findings that BPA exposure can reduce sex differences in brain and some behaviors. We asked if a low BPA dose, within the range measured in humans, ingested during pregnancy, would affect social behaviors in prepubertal mice. We noted sex differences in social interactions whereby females spent more time sitting side-by-side, while males engaged in more exploring and sitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 76 publications
9
90
0
Order By: Relevance
“…Continuous BPA exposure during this period has been shown to have profound effects on the brain and behavior [8], leading to altered learning and memory [9][10][11], hyperactivity [12], increased expression of anxiety, and aggression [11]. As such, early BPA exposure (EBE) has been linked to the development of some neuropsychiatric disorders such as autism, schizophrenia in the later life [12][13][14]. Studies in the past decade have demonstrated that many of its adverse effects on the brain are associated with the ability of BPA to disrupt estrogen receptor (ER) signaling in developing neurons leading to aberrant neuronal proliferation and differentiation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous BPA exposure during this period has been shown to have profound effects on the brain and behavior [8], leading to altered learning and memory [9][10][11], hyperactivity [12], increased expression of anxiety, and aggression [11]. As such, early BPA exposure (EBE) has been linked to the development of some neuropsychiatric disorders such as autism, schizophrenia in the later life [12][13][14]. Studies in the past decade have demonstrated that many of its adverse effects on the brain are associated with the ability of BPA to disrupt estrogen receptor (ER) signaling in developing neurons leading to aberrant neuronal proliferation and differentiation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in animals (mostly rodents) have shown that low doses of BPA 538 can disrupt the development of sexually dimorphic behaviors, including anxiety, social 539 interaction, aggression, and spatial memory, and that this disruption has distinct effects 540 on males and females (Adriani et al 2003;Gioiosa et al 2013;Palanza et al 2008;541 Rubin et al 2006;Rosenfeld et al 2012;Wolstenholme et al 2011a and2011b).…”
mentioning
confidence: 99%
“…Brains from 18.5 days post-coitus male mice exposed to BPA express less oxytocin, oxytocin receptor gene expression, and vasopressin than control males [28] . In their study, expression of oxytocin receptor gene in brain of female mice was higher than control that is consistent with our finding in uterine.…”
Section: Discussionmentioning
confidence: 88%